Las religiones a juicio y Bertrand Russell de fiscal. - Guevara Arroyo, Alejandro (2013)
Exposition of several contemporary theses infavor of the divine existence and of the Christian dogmas. In addition, the suit abilityof both positions will be checked critically, by means of arguments of Russell himself, of the analytic philosophy, of the critical rationalism philosophy and of the science. Finally, one will present the attitude of the free thinker, defendedby Russell and its importance in philosophical reflection.